A comparison of the time course of action and laryngeal mask airway insertion conditions with different doses of mivacurium for day-case urologic surgery in children: a prospective cohort study - Ye, Hong; Nian, Chunmiao; Zhou, Lijun; Xie, Yuman; Li, Fan; Xue, Tao; Han, Xueping (Frontiers in Pediatrics, 2024)
Objective: To investigate the time course of action of different doses of mivacurium and determine the appropriate dose for laryngeal mask airway (LMA) insertion for day-case urologic surgery in children. Methods: A total of 105 patients who enrolled in this study between March 2021 and December 2021 were randomised into 3 groups: Group A (mivacurium 0.15 mg/kg, n = 35), Group B (mivacurium 0.20 mg/kg, n = 35) and Group C (mivacurium 0.25 mg/kg, n = 35). The different doses of mivacurium were injected before LMA insertion. The primary outcomes included the grading of conditions for the LMA insertion-18 score, onset time, recovery index and the duration that mivacurium was effective. Secondary outcomes included pulse oxygen saturation, mean blood pressure, heart rate and the incidence of adverse events. Results: The score of the conditions for LMA insertion in Group A was significantly lower than in Groups C and B (p < 0.005). There was a significant difference in the onset time between Groups B and A (p < 0.005). There was no significant difference in the overall incidence of adverse reactions between these groups (p > 0.05). Conclusion: Anaesthesia with 0.2 mg/kg of mivacurium can effectively shorten the onset time and facilitate insertion of the LMA in children undergoing day-case urologic surgery.